2011
DOI: 10.3892/ijo.2011.898
|View full text |Cite
|
Sign up to set email alerts
|

Ganodermanontriol, a lanostanoid triterpene from Ganoderma lucidum, suppresses growth of colon cancer cells through ß-catenin signaling

Abstract: Abstract. Colorectal cancer is one of the most common cancers in men and women in the world. Previous molecular studies have revealed that deregulation of the ß-catenin signaling pathway plays a crucial role in the progression of colorectal cancer. Therefore, modulation of the ß-catenin pathway offers a strategy to control colorectal cancer progression. The medicinal mushroom Ganoderma lucidum (GL) is a rich source of triterpenes with anticancer properties. Here, we show that ganodermanontriol (GNDT), a purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Numerous studies have revealed that the primary active ingredients of G. lucidum are polysaccharides and the secondary metabolites ganoderic acids (GAs) [3], [4]. Most GAs have important medicinal value, such as the regulation of osteoclast genesis [5], the inhibition of cholesterol synthesis [3] and tumor growth [6], and protection of the liver [7]. However, despite the important pharmacological potential of GAs, low GA yield from both field cultivation and fermentation limits its wide-spread use.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed that the primary active ingredients of G. lucidum are polysaccharides and the secondary metabolites ganoderic acids (GAs) [3], [4]. Most GAs have important medicinal value, such as the regulation of osteoclast genesis [5], the inhibition of cholesterol synthesis [3] and tumor growth [6], and protection of the liver [7]. However, despite the important pharmacological potential of GAs, low GA yield from both field cultivation and fermentation limits its wide-spread use.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that G. lucidum extracts exert anticancer effects. 319 However, the mechanism behind the anticancer action is not well understood. mTOR plays a pivotal role in controlling cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 G. lucidum and its extracts have been documented as potential anticancer agents for various tumors, including those in melanoma, 3,4 leukemia, lymphoma, myeloma, 5,6 breast cancer, 4–7 prostate cancer, 4–8 ovarian cancer, 9 bladder cancer, 10 head and neck cancer, 11 lung cancer, 1214 liver cancer, 15,16 gastric cancer, 17 and colon cancer. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderic bio-compounds have demonstrated various anti-proliferative and cytotoxic effects in studies regarding the treatment of different types of cancer [252][253][254][255]. The anti-proliferative effects of Gl-Ts compounds in G. lucidum manifest through cell cycle arrest [252,253].…”
Section: Anti-proliferative Cytotoxic and Apoptosis-increasing Activi...mentioning
confidence: 99%